Peran Kepemimpinan Transformasional dan Integritas Terhadap Kinerja Karyawan - Irfan Aziz Hilmy; Renno Adrian; Shaif Iqbal (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Employee performance is a key indicator for an employee in fulfilling their duties and responsibilities. A company leader with a transformational leadership style is expected to inspire and motivate employees to develop and contribute to achieving the company's goals. Combined with employee integrity, employees are required to have honesty, responsibility, and consistency in their duties. This research aims to determine how much the role of transformational leadership can foster an attitude of honesty at work, responsibility to the job, and consistency in performing duties to maximize company performance. Data collection techniques use qualitative methods, with in-depth interviews with employees. The total number of respondents is 7 employees, 2 managers, and 1 HRD. Interviews were conducted 4 times with 3 respondents in employee positions to confirm data at the state-owned enterprise PT. PNM (Persero) Sunyaragi Branch located in Cirebon City. The study results show that the role of a company leader with a transformational style can foster integrity among employees, demonstrating good performance for the company. With integrity, employees can exhibit an open attitude towards their superiors and professionalism in their work.